#337 : Six Characters of Seminiferous Tubules Appearances During Micro-Tese Related with Different Sperm Retrieval Rate - Jing Zhang; Hong Chen; LuGang Zhao; GuiHua Liu; XiaoYan Liang; Cong Fang (Fertility & Reproduction, 2023)
Background and Aims: For non-obstructive azoospermia (NOA) patients, micro-TESE is considered to have higher sperm retrieval rate (SRR) than traditional surgery. However, various clinical parameters are not reliable predictors for the presence of focal spermatogenesis and SRR. This study summarized the characters of seminiferous tubules appearances and investigated their relationship with SRR. Method: This was a retrospective study. From September 2014 to April 2023, 638 NOA patients treated with micro-TESE were divided into six groups according to the seminiferous tubules appearances (Group-A: homogeneously thick, Group-B: homogeneously thin, Group-C: seminiferous tubules were severe thin and loss the tubal appearance, Group-D: the testicles were filled with hyperplastic Leydig cells, seminiferous tubules were severe thin and rare, Group-E, thick tubules mixed with thin tubules, Group-F, extensive testicular microlithiasis). Age, testicular volume, serum FSH, testosterone level, SRR and the heterogeneous seminiferous tubules presenting rate (HSTPR) were compared. Results: Sperms were successfully retrieved in 333 cases (SRR=52.2%). There were no statistical differences in age, testicular volume, FSH and testosterone level between the patients who succeeded and failed to obtain sperm (Table 1, all [Formula: see text]>0.05). The constituent ratio of etiology was different in the six groups (Table 2, [Formula: see text]<0.05). Between the six groups, testicular volume, FSH, testosterone, SRR and HSTPR were statistically different (Table 3, all [Formula: see text]<0.05). Conclusion: Age, testicular volume, FSH and testosterone were insufficient to predict the SRR of NOA patients. Micro-TESE is commended to terminated when sperm are retrieved in case that the seminiferous tubules are rare or too thin to present tubal appearance, thick tubules mix with thin tubules or extensive testicular microlithiasis present (Group C-F). If the tubules appear homogeneously thick or thin, micro-TESE would has less advantage comparing with conventional multiple TESE because of the difficulty to identify the differences between the tubules even if the sperm is finally retrieved (Group A-B).